Nutritional status and food security of socially vulnerable families in the municipality of Contagem, Minas Gerais, 2014 - Oliveira, Dirce Ribeiro de; Ribeiro, Mayana Rodrigues dos Santos; Rodrigues, Márcia Christiane Oliveira; Cruz, Ruth Elizabeth; Santos, Joseph Fabiano Guimarães; Barros, Raphael Tobias de Vasconcelos; Geiger, Stefan Michael; Gomes, Maria Aparecida (O Mundo da Saúde, 2023)
This is a cross-sectional study evaluating nutritional status and food insecurity in a vulnerable community in Contagem, in the metropolitan region of Belo Horizonte. A total of 273 individuals from 67 families were evaluated. For the anthropometric assessment, weight, height, body mass index, waist circumference, and waist-to-height ratio were determined. Food insecurity was analyzed using the Brazilian Food Insecurity Scale. Total cholesterol, triglycerides, glucose, and serum albumin concentrations were also determined. Of the 67 families evaluated, 51% (n = 34) had food insecurity, of which 79.4% were mild, 17.7% were moderate, and 2.9% were severe. In children and adolescents, overweight and obesity were diagnosed in 9.3% (n = 4) and 19.5% (n = 16), respectively. Among adults, 34.1% (n = 42) were classified as overweight, 27.6% (n = 34) had grade I obesity, and 59.3% (n = 73) had an increased risk of cardiovascular disease. In the elderly, overweight was diagnosed in 44.0% (n = 11), and 80.0% (n = 20) had an increased risk for cardiovascular diseases. Hyperglycemia, hypercholesterolemia, and hypertriglyceridemia were diagnosed in 17, 45, and 72% of the population, respectively. There was a positive correlation between anthropometric and biochemical parameters, with the exception of albumin and glucose, which showed a negative correlation in children and adults. Our study confirms the impact of social vulnerability on the occurrence of high proportions of food insecurity, leading to a high prevalence of overweight and obesity and an increased risk for cardiovascular disorders. Furthermore, our findings support the use of serum albumin concentrations as an indicator of changes in glucose metabolism.